Fractures of implant fixtures: a retroscccpective clinical study - Han-Chang Yu; Young-Kyun Kim (SpringerOpen, 2020)
Abstract Background The aim of this study was to evaluate the factors that may affect implant fixture fractures. Methods Patients who experienced implant fixture removal at Seoul National University Bundang Hospital from 2007 to 2015 due to implant fixture fracture were included. Implant/crown ratio, time of implant fracture, clinical symptoms before implant fracture, treatment of fractured implants, and the success and survival rate of the replaced implants were evaluated retrospectively. Results Thirteen implants were fractured in 12 patients. Patient mean age at the time of fracture was 59.3 years. Of the 13 implants, 7 implants were placed at our hospital, and 6 were placed at a local clinic. The mean crown/implant ratio was 0.83:1. The clinical symptoms before fracture were screw loosening in five implants, marginal bone loss in five implants, and the presence of peri-implant diseases in five implants. All the fractured implants were removed, and 12 out of the 13 sites were re-implanted. Parafunctions were observed in two patients: one with bruxism and one with attrition due to a strong chewing habit. Conclusions Several clinical symptoms before the fracture of an implant can predict implant fixture failure. Therefore, if these clinical symptoms are observed, appropriate treatments can be taken before more serious complications result.